Composite gradient structure coating on Ta-based refractory metal surface and preparation method of composite gradient structure coating
By preparing the composite gradient structure coating on the surface of the TA base, it solves the problem of poor antioxidant properties at high temperature at high temperature, extend the service life of the coating and improves high temperature protection performance.
Patent Information
- Application Number
- CN202411445756.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-10-16
AI Technical Summary
Tantalum and tantalum alloys have poor oxidation resistance under high temperature environments, resulting in accelerated oxidation above 500℃, affecting their application life. At the same time, the existing Ir coatings have problems with micropore diffusion and oxidation volatility at high temperatures, resulting in premature failure.
A composite gradient structural coating is used on the Ta-based refractory metal surface, including a base layer, a diffusion barrier layer, a transition layer and a thermal protection layer. These layers are deposited by magnetron sputtering technology to form a gradient structure to improve the bonding strength and oxidation resistance of the coating.
It extends the service life of the coating under working conditions, improves the bonding strength between the coating and the substrate, enhances the overall high-temperature protection performance, and solves the problems of structural instability and oxidative volatilization of the Ir coating at high temperatures.
Smart Images

Figure CN119332216A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of thermal protection coating materials, and in particular to a composite gradient structure coating on the surface of a Ta-based refractory metal and a preparation method thereof. Background Art
[0002] Hypersonic aircraft refers to aircraft with a cruising speed exceeding Mach 5 and can reach a battlefield 5,000 kilometers away within 1 hour. It has the advantages of good concealment, strong penetration capability, high combat effectiveness and a wide combat space. It can achieve strategic goals such as precision strikes, rapid transportation, and long-range real-time reconnaissance, and has important research significance.
[0003] Compared with the service environment of traditional aircraft, the service environment of hypersonic aircraft may exceed 1600℃ under the condition of atmospheric re-entry. The thermal environment of hypersonic aircraft includes ultra-high temperature greater than 2000℃, large thermal gradient and stress, and greater than 10MW·m -2 The thermal protection systems used in these areas are highly chemically active gas flows and complex thermo-mechanical loads. Therefore, the materials used in these areas must be able to withstand the extremely high temperatures and strong heat fluxes associated with large mechanical stresses. Therefore, it is very important to develop thermal protection systems with good oxidation resistance, thermal shock resistance, ablation resistance and dimensional stability.
[0004] Tantalum and tantalum alloys have the advantages of high melting point, good corrosion resistance, excellent high temperature strength, good processing performance, weldability, low plastic / brittle transition and excellent dynamic mechanical properties. At a high temperature of 2000℃, they have excellent tensile strength, high temperature creep resistance and high temperature endurance performance. They are an ideal structural material working in an environment of 1600℃~1800℃ and have very important applications in the aerospace field. Although tantalum and tantalum alloys have excellent high temperature mechanical properties, their oxidation resistance at high temperatures is poor. Metal tantalum will undergo accelerated oxidation to generate Ta2O5 above 500℃, and the higher the temperature, the more severe the oxidation until it is completely pulverized and destroyed. This shortcoming limits the application of tantalum and tantalum alloys. In order to improve the service life of the alloy at high temperature, the most effective method is to prepare a protective coating on the surface of the alloy. The surface coating can have the advantages of low oxygen permeability, good chemical and physical compatibility and stability, low volatility, good thermal expansion coefficient matching and bonding ability, high temperature self-healing ability and can not affect the original good mechanical properties of the tantalum alloy substrate. It is the best way to solve the problems of high temperature mechanical properties and oxidation resistance of tantalum alloys.
[0005] Iridium metal has good corrosion resistance and is insoluble in sulfuric acid, hydrochloric acid, nitric acid, hydrofluoric acid and sodium hydroxide melt. It has good chemical stability and extremely low oxygen permeability, which remains basically unchanged with increasing temperature. It also has excellent high-temperature mechanical stability. At 1800°C, 1μm of Ir has an oxygen permeability resistance equivalent to 1mm of SiO2; therefore, Ir is considered to be one of the most ideal high-temperature antioxidant coating materials above 1800°C.
[0006] Although Ir coatings are used in high-temperature oxidation-resistant coatings because of their extremely low oxygen permeability, pure Ir still has some problems when used, which have a great impact on its service life. Ir coatings mainly face two problems during service: (1) The phenomenon of microporous diffusion and aggregation along grain boundaries in Ir coatings will lead to the formation of rapid diffusion pathways at grain boundaries, providing almost the shortest diffusion path for oxygen elements and matrix elements, and the coating will fail prematurely. (2) Ir coatings have defects in high-temperature oxidation characteristics. On the one hand, iridium oxidizes and volatilizes in the form of IrO2 and IrO3 at temperatures above 1100°C, resulting in continuous thinning of the coating; on the other hand, Ir has high catalytic activity and low thermal radiation rate, which causes the surface temperature of the iridium coating to rise sharply, exacerbating the oxidation, volatilization and ablation of Ir. Therefore, it is necessary to modify the Ir coating according to the organizational structure characteristics and high-temperature oxidation characteristics of Ir to improve the high-temperature oxidation resistance of the coating. Summary of the invention
[0007] In order to solve the above technical problems, the present invention provides a composite gradient structure coating on the surface of a Ta-based refractory metal and a preparation method thereof.
[0008] The composite gradient structure coating on the surface of a Ta-based refractory metal and the preparation method thereof of the present invention are realized by the following technical solutions:
[0009] During the research process, the present invention found that if the high-temperature oxidation resistance of the Ir coating is improved by directly changing only the preparation process to optimize the coating structure, since the working temperature of Ir is much higher than its recrystallization temperature, the grains of the Ir coating grow rapidly during use, and its grain boundary structure cannot remain stable for a long time. In addition, changing the structure cannot slow down the oxidation volatilization rate of the Ir coating. Therefore, simply optimizing the Ir coating structure by changing the preparation process has limited improvement on the oxidation resistance life of the Ir coating.
[0010] If the performance of the Ir coating is improved by directly setting a layer of ceramic coating with high melting point, low thermal conductivity and high emissivity on the surface of the Ir coating, the ceramic coating can directly block the contact between iridium and the external environment and thus reduce the surface temperature of the coating; however, some ceramic coatings such as HfO2 and ZrO2 undergo solid-state phase change during the heating process, resulting in volume change and internal stress, which causes the bonding between the ceramic layer and the Ir coating to deteriorate and eventually peel off; or the micropores and cracks generated in the ceramic coating during service cannot be healed, and the defects continue to grow until the protective effect on the Ir coating is lost, that is, it is difficult to effectively improve the high-temperature oxidation resistance of the Ir coating by setting a ceramic coating.
[0011] If the performance of the Ir coating is improved by directly alloying the surface of the Ir coating with alloying elements such as Hf, Zr, Ta and Al, these alloying elements will be continuously oxidized in a high-temperature oxidizing environment to form a dense refractory oxide outer layer, thereby protecting the Ir coating; however, after the alloying elements are oxidized, a denser oxide outer layer is generated in situ. Due to the mismatch of physical parameters such as the thermal expansion coefficient, the oxide layer is prone to cracking and falling off, thereby losing its protective effect.
[0012] Therefore, based on the above research, in order to extend the service life of the coating under working conditions and improve the bonding strength between the coating and the substrate, the present invention provides a Ta-based refractory metal surface composite gradient structure coating, wherein the composite gradient structure coating is arranged on the Ta substrate, and the composite gradient structure coating includes a base layer, a diffusion barrier layer, a transition layer and a thermal protection layer which are stacked in sequence from the inside to the outside on the Ta substrate.
[0013] The composition of the base layer is metal or metal carbide, and the bias voltage of the base layer gradually decreases from the inside to the outside on the Ta substrate. The change of bias voltage can play a transitional role, avoiding the generation of abrupt interfaces, so as to improve the bonding strength between the coating and the substrate.
[0014] The diffusion barrier layer is made of metal carbide, which has good high temperature stability and chemical stability, so as to prevent Ta from diffusing outward.
[0015] The transition layer is composed of metal carbides and Re; and in the transition layer, the content of metal carbides decreases gradually from the inside to the outside, and the content of Re increases gradually from the inside to the outside, so as to improve the bonding force between the barrier layer and the thermal protection layer.
[0016] The thermal protection layer is composed of a Re layer, an Ir layer and a HfO2-Y2O3 layer from the inside to the outside. The layers are arranged in sequence to prevent the diffusion of the Ta element of the substrate and the Ir element of the coating, alleviate the difference in thermal expansion coefficients between the Ir and the ceramic layer, and improve the bonding strength of the coating.
[0017] In some preferred embodiments of the present invention, the thickness of the Re layer is 400nm to 500nm. In some preferred embodiments of the present invention, the thickness of the Ir layer is 800nm to 1500nm. In some preferred embodiments of the present invention, the thickness of the HfO2-Y2O3 layer is 100nm to 300nm.
[0018] In some preferred embodiments of the present invention, the metal is one or both of Re and Ta.
[0019] In some preferred embodiments of the present invention, the metal carbide is one or both of HfC and TaC.
[0020] In some preferred embodiments of the present invention, the thickness of the primer layer is 100 nm to 500 nm.
[0021] In some preferred embodiments of the present invention, the thickness of the diffusion barrier layer is 100 nm to 500 nm.
[0022] In some preferred embodiments of the present invention, the thickness of the transition layer is 50 nm to 500 nm.
[0023] The present invention takes into account that traditional coatings are mainly prepared by methods such as infiltration, thermal spraying, chemical vapor deposition and electrodeposition. However, in the above-mentioned preparation methods, the coating thickness and uniformity of the infiltration and thermal spraying methods are not easy to control; the chemical vapor deposition product is toxic and seriously corrodes the equipment, the electrodeposition coating has large stress and is easy to crack, and the coating often has pinhole defects and other problems. In addition, the three main modification methods of Ir coatings currently include optimizing the coating structure, coating with ceramic coatings and surface alloying, but each single modification method has its own limitations. Optimizing the Ir coating structure by changing the process has limited improvement in the anti-oxidation life of the Ir coating, and the latter two methods both have problems such as mismatching of the thermal expansion coefficients of Ir and the ceramic layer and poor bonding. Therefore, the present invention adopts magnetron sputtering technology to prepare a coating with a composite gradient structure on the surface of the Ta substrate by magnetron sputtering to reduce the formation of volatile oxides of iridium, improve the bonding strength of the coating, extend the service life of the coating, and enhance the overall high-temperature protection performance of the coating. And the preparation method of the present invention includes the following steps:
[0024] Step 1, pretreatment of Ta substrate:
[0025] The Ta substrate is polished and then cleaned to obtain a pretreated Ta substrate.
[0026] It should be noted that the present invention takes into account the possible presence of impurities such as oil stains and surface defects on the surface of the Ta substrate, so it is first polished and then cleaned to remove impurities on the surface of the Ta substrate and improve its surface roughness, so as to improve the bonding strength between the Ta substrate surface and the coating.
[0027] It should also be noted that since the subsequent glow sputtering cleaning treatment and the magnetron sputtering process in each step are carried out in the magnetron sputtering equipment, the pre-treated Ta substrate is installed on the workpiece turntable in the vacuum chamber of the magnetron sputtering equipment to facilitate the subsequent deposition of the base layer, diffusion barrier layer, transition layer and thermal protection layer.
[0028] Step 2, glow sputtering cleaning process:
[0029] The pretreated Ta substrate is subjected to glow sputtering cleaning treatment to obtain a clean Ta substrate.
[0030] It should be noted that, considering that the pretreated Ta substrate may still contain impurities such as oxides, the present invention further performs glow sputtering cleaning on the pretreated Ta substrate to further improve the bonding strength between the Ta substrate surface and the coating.
[0031] Step 3, deposit the base layer:
[0032] In an argon atmosphere, magnetron sputtering technology is adopted, a metal target or a metal carbide target is used as a sputtering target, and the substrate bias is controlled to gradually decrease, and a primer layer is deposited on the surface of the clean Ta substrate.
[0033] It should be noted that the present invention controls the substrate bias to gradually decrease so as to deposit a coating layer with a reduced bias gradient on the surface of the Ta substrate. That is, the coating layer formed by the present invention is formed by a plurality of different coating layer gradient composites. Compared with the coating layer with uniform component distribution, the gradient distribution coating layer can play a role of slow transition and avoid sudden interface, thereby effectively solving the problem that the grain boundary structure of the Ir coating cannot remain stable for a long time and the interface bonding is poor, thereby improving the service life of the Ir coating on the Ta substrate under working conditions.
[0034] Step 4, depositing a diffusion barrier layer:
[0035] A metal carbide target is used as a sputtering target material, and a diffusion barrier layer is deposited on the surface of the base layer.
[0036] It should be noted that the present invention deposits a metal carbide layer on the surface of the base layer as a diffusion barrier layer to prevent Ta from diffusing outwards through the metal carbide, thereby preventing Ta from diffusing to the outermost surface of the coating and being oxidized into oxides during service, thereby avoiding the mismatch in thermal expansion coefficients between the coating and the substrate, thereby achieving the goal of extending the service life of the coating under working conditions while improving the bonding strength between the coating and the substrate.
[0037] Step 5, deposition of transition layer:
[0038] A metal carbide target and a Re target are used as co-sputtering targets and deposited on the surface of the diffusion barrier layer at the same time. During the deposition process, the sputtering power of the metal carbide target is gradually reduced and the sputtering power of the Re target is gradually increased to deposit a transition layer with a decreasing metal carbide component gradient and an increasing Re component gradient on the surface of the diffusion barrier layer.
[0039] It should be noted that the present invention further deposits a transition layer with a component gradient distribution on the surface of the diffusion barrier layer. The transition layer can not only effectively prevent the Ta element of the matrix from diffusing outward, but also improve the bonding strength between the various coatings, thereby effectively improving the overall high-temperature protection performance and service life of the coating.
[0040] Step 6, depositing a thermal protection layer:
[0041] A Re target, an Ir target and a HfO2-Y2O3 target are used as sputtering targets in sequence, and a Re layer, an Ir layer and a HfO2-Y2O3 layer are deposited in sequence on the surface of the transition layer to form a thermal protection layer composited by a Re layer, an Ir layer and a HfO2-Y2O3 layer on the surface of the transition layer.
[0042] It should be noted that the present invention deposits the Re layer, the Ir layer and the HfO2-Y2O3 layer in sequence to further prevent the diffusion of the Ta element in the matrix and the Ir element in the coating, alleviate the difference in thermal expansion coefficients between the Ir and the ceramic layer, improve the bonding strength of the coating, and thus achieve the effect of high temperature protection.
[0043] It should also be noted that in the above steps 3 to 6, the present invention adopts high vacuum magnetron sputtering technology. Due to the use of magnetron sputtering technology, the morphology, structure and thickness of the coating can be accurately controlled, and the co-sputtering technology can achieve a composition gradient structure of the coating, thereby forming a composite gradient structure coating on the Ta-based refractory metal, and the coating is tightly bonded to each other and to the substrate, which can effectively reduce the formation of volatile oxides of iridium, thereby improving the overall high-temperature protection performance of the coating, and solves the problems of optimizing the microstructure of the Ir coating, covering the surface of the iridium coating with a ceramic layer, or in-situ generating an oxide ceramic layer by alloying, such as the inability to maintain stability of the grain boundary structure for a long time and poor interface bonding.
[0044] In some preferred embodiments of the present invention, when depositing the base layer, the vacuum is first evacuated to a background vacuum of ≤5×10 -4 Pa, and then introduce argon to maintain the working gas pressure at 0.2Pa~1.5Pa; and during sputtering deposition, the fixed sputtering power is 200W~300W, and the argon gas flow rate is 10sccm~30sccm; first, under the condition of a substrate bias voltage of -400V~-500V, a first primer layer with a thickness of 20nm~100nm is deposited; then the substrate bias voltage is adjusted to -300V~-400V, and a second primer layer with a thickness of 20nm~100nm is deposited; then the substrate bias voltage is adjusted to -200V~-300V, and a third primer layer with a thickness of 20nm~100nm is deposited; finally, the substrate bias voltage is adjusted to -100V~-200V, and a fourth primer layer with a thickness of 20nm~100nm is deposited, so that the first primer layer, the second primer layer, the third primer layer and the fourth primer layer distributed by the gradient are used together as the primer layer, so as to further improve the improvement effect of the primer layer on the bonding force between the coating and the substrate.
[0045] In some preferred embodiments of the present invention, when depositing the diffusion barrier layer, argon gas is introduced, and the argon gas flow rate is controlled to be 10sccm~30sccm, and the working gas pressure is controlled to be 0.2Pa~1.5Pa; the sputtering power is 200W~300W, and the substrate bias is -90V~-120V, so as to further improve the diffusion barrier layer's barrier effect on the outward diffusion of Ta.
[0046] In some preferred embodiments of the present invention, when depositing the transition layer, argon gas is introduced, the argon gas flow rate is controlled to be 10sccm~30sccm, the working gas pressure is controlled to be 0.2Pa~1.5Pa, and the substrate bias is fixed to be -90V~-120V; first, under the condition that the sputtering power of the metal carbide target is 200W~300W and the sputtering power of the Re target is 50W~100W, a first transition layer with a thickness of 20nm~100nm is deposited; then, under the condition that the sputtering power of the metal carbide target is adjusted to 100W~200W and the sputtering power of the Re target is 100W~150W, a layer with a thickness of 20nm~100nm is deposited. The second transition layer is formed by adjusting the sputtering power of the metal carbide target to 50W-100W and the sputtering power of the Re target to 150W-200W, and depositing a third transition layer with a thickness of 20nm-100nm; finally, the sputtering power of the metal carbide target is adjusted to 20W-50W and the sputtering power of the Re target is adjusted to 200W-250W, and depositing a fourth transition layer with a thickness of 20nm-100nm, so that the first transition layer, the second transition layer, the third transition layer and the fourth transition layer with gradient distribution are combined as a transition layer to further effectively prevent the Ta element of the matrix from diffusing outward and further improve the bonding force between each coating.
[0047] In some preferred embodiments of the present invention, when depositing the thermal protection layer, argon gas is introduced, the argon gas flow rate is controlled to be 10sccm~30sccm, the working gas pressure is controlled to be 0.2Pa~1.5Pa, and the substrate bias is -90V~-120V; when depositing the Re layer in the thermal protection layer, the sputtering power is 200W~250W; when depositing the Ir layer in the thermal protection layer, the sputtering power is 200W~300W; when depositing the HfO2-Y2O3 layer in the thermal protection layer, the sputtering power is 200W~300W.
[0048] In some preferred embodiments of the present invention, during the glow sputtering cleaning process, the vacuum is first evacuated to a background vacuum of ≤5×10 -4 Pa, then introduce argon, control the argon flow rate to 10sccm~30sccm, control and maintain the working gas pressure to 0.2Pa~1.5Pa, the substrate bias voltage to -300V~-500V, and the cleaning time ≥15min.
[0049] In some preferred embodiments of the present invention, the pretreated Ta substrate is obtained by the following steps: the Ta substrate is polished with 400#, 800#, 1500#, 2000#, and 3000# sandpaper in sequence, and then mechanically polished with 0.5μm, 0.25μm, and 0.05μm diamond polishing agents in sequence until the surface is smooth and free of obvious scratches, and then ultrasonically cleaned with acetone and anhydrous ethanol in sequence for 10min to 15min and then dried to obtain the pretreated Ta substrate.
[0050] Compared with the prior art, the present invention has the following beneficial effects:
[0051] The composite gradient structure coating of the present invention includes a base layer, a diffusion barrier layer, a transition layer and a thermal protection layer stacked in sequence from the inside to the outside on a Ta substrate. Among them, the base layer is composed of metal or metal carbide, and the bias of the base layer on the Ta substrate gradually decreases from the inside to the outside to improve the bonding strength between the coating and the substrate. The diffusion barrier layer is composed of metal carbide to prevent Ta from diffusing outward. The transition layer is composed of metal carbide and Re; and in the transition layer, the content of metal carbide decreases from the inside to the outside in a gradient, and the content of Re increases from the inside to the outside in a gradient. The thermal protection layer is composed of a Re layer, an Ir layer and a HfO2-Y2O3 layer from the inside to the outside. By arranging each layer in sequence, the diffusion of the substrate Ta element and the coating Ir element can be prevented, the difference in thermal expansion coefficients between Ir and the ceramic layer can be alleviated, the bonding strength of the coating can be improved, and the service life of the thermal protection coating and the substrate can be improved.
[0052] The present invention combines a variety of high-temperature resistant ablation coatings in a gradient structure, thereby overcoming the defects of a single component and greatly improving the corrosion resistance of the Ir coating on the surface of a Ta-based refractory alloy substrate; compared with a single-component coating, the coating with a composite gradient structure can reduce the formation of volatile oxides of iridium, increase the bonding strength of the coating, extend the service life of the coating, and enhance the overall high-temperature protection performance of the coating.
[0053] The present invention adopts high vacuum magnetron sputtering technology to prepare a thermal protection coating with a composite gradient structure on a Ta-based refractory metal, thereby avoiding the problems that the coating thickness and uniformity of the infiltration method and the thermal spraying method are difficult to control, the products of the chemical vapor deposition method are toxic and seriously corrode the equipment, the coating of the electrodeposition method has large stress and is easy to crack, and the coating often has pinhole defects. In addition, the coating is tightly bonded between the layers and with the substrate, which can effectively reduce the formation of volatile oxides of the iridium element, thereby improving the overall high-temperature protection performance of the coating, and solves the problems existing in methods such as optimizing the organizational structure of the Ir coating, covering the surface of the iridium coating with a ceramic layer, or in-situ generating an oxide ceramic layer by alloying, such as the inability to maintain a stable grain boundary structure for a long time and poor interface bonding.
[0054] Compared with traditional coatings, the thermal protection coating with a composite gradient structure prepared by magnetron sputtering technology in the present invention effectively solves the problems that the grain boundary structure of the Ir coating cannot remain stable for a long time and the interface bonding is poor, thereby improving the service life of the Ir coating on the Ta substrate under working conditions.
[0055] In the preparation process of the present invention, due to the use of magnetron sputtering technology, the morphology, structure and thickness of the coating can be accurately controlled, and the co-sputtering technology can realize the composition gradient structure of the coating. The multi-layer composite diffusion barrier layer prevents the diffusion of the Ta element of the substrate and the Ir element of the coating, thereby improving the service life of the thermal protection coating and the substrate.
[0056] Compared with the method of optimizing the organizational structure of the Ir coating, the preparation method of the present invention has a simple process and is easy to operate, and the structure and composition between each layer are easy to control, which can increase the service life of the coating.
[0057] Compared with the method of surface covering with a ceramic layer and surface alloying, the preparation method of the present invention can alleviate the difference in thermal expansion coefficients between the Ir and the ceramic layer and improve the bonding strength of the coating. BRIEF DESCRIPTION OF THE DRAWINGS
[0058] Figure 1 It is a schematic diagram of the structure of the composite gradient structure coating of the present invention.
[0059] Figure 2 This is a cross-sectional scanning electron microscope image of the composite gradient structure coating prepared in Example 4.
[0060] Figure 3 This is the XRD spectrum of the composite gradient structure coating prepared in Example 5.
[0061] Figure 4 This is a cross-sectional scanning electron microscope image of the composite gradient structure coating prepared in Example 6 after high-temperature annealing.
[0062] Figure 5 The scratch backscattering images of the composite gradient structure coating prepared in Example 6 before and after high-temperature annealing and after the scratch test; wherein, (a) is the scratch backscattering image of the composite gradient structure coating prepared in Example 6 before and after the scratch test; (b) is the scratch backscattering image of the composite gradient structure coating prepared in Example 6 after the high-temperature annealing and after the scratch test.
[0063] Figure 6 This is a cross-sectional scanning electron microscope image of the coating prepared in Comparative Example 3 after high temperature annealing. DETAILED DESCRIPTION
[0064] The technical solutions in the embodiments of the present invention will be described clearly and completely below.
[0065] Example 1
[0066] See also Figure 1 , this embodiment provides a composite gradient structure coating on the surface of a Ta-based refractory metal.
[0067] The composite gradient structure coating of the present embodiment includes a primer layer, a diffusion barrier layer, a transition layer and a thermal protection layer which are sequentially stacked from the inside to the outside on a Ta substrate.
[0068] In this embodiment, the composition of the base layer is HfC.
[0069] In this embodiment, the component of the diffusion barrier layer is HfC.
[0070] In this embodiment, the transition layer is composed of HfC and Re; and in the transition layer, the content of metal carbides decreases gradually from the inside to the outside, and the content of Re increases gradually from the inside to the outside;
[0071] In this embodiment, the thermal protection layer is composed of a Re layer, an Ir layer and a HfO2-Y2O3 layer from the inside to the outside; wherein the thickness of the Re layer is 400nm to 500nm; the thickness of the Ir layer is 800nm to 1500nm; and the thickness of the HfO2-Y2O3 layer is 100nm to 300nm.
[0072] Example 2
[0073] This embodiment provides a composite gradient structure coating on the surface of a Ta-based refractory metal.
[0074] The composite gradient structure coating of the present embodiment includes a primer layer, a diffusion barrier layer, a transition layer and a thermal protection layer which are sequentially stacked from the inside to the outside on a Ta substrate.
[0075] In this embodiment, the composition of the primer layer is Re.
[0076] In this embodiment, the component of the diffusion barrier layer is HfC.
[0077] In this embodiment, the transition layer is composed of HfC and Re; and in the transition layer, the content of metal carbides decreases gradually from the inside to the outside, and the content of Re increases gradually from the inside to the outside;
[0078] In this embodiment, the thermal protection layer is composed of a Re layer, an Ir layer and a HfO2-Y2O3 layer from the inside to the outside; wherein the thickness of the Re layer is 400nm to 500nm; the thickness of the Ir layer is 800nm to 1500nm; and the thickness of the HfO2-Y2O3 layer is 100nm to 300nm.
[0079] Example 3
[0080] The composite gradient structure coating of the present embodiment includes a primer layer, a diffusion barrier layer, a transition layer and a thermal protection layer which are sequentially stacked from the inside to the outside on a Ta substrate.
[0081] In this embodiment, the composition of the base layer is Ta.
[0082] In this embodiment, the component of the diffusion barrier layer is HfC.
[0083] In this embodiment, the transition layer is composed of HfC and Re; and in the transition layer, the content of metal carbides decreases gradually from the inside to the outside, and the content of Re increases gradually from the inside to the outside;
[0084] In this embodiment, the thermal protection layer is composed of a Re layer, an Ir layer and a HfO2-Y2O3 layer from the inside to the outside; wherein the thickness of the Re layer is 400nm to 500nm; the thickness of the Ir layer is 800nm to 1500nm; and the thickness of the HfO2-Y2O3 layer is 100nm to 300nm.
[0085] Example 4
[0086] This embodiment provides a method for preparing a composite gradient structure coating on the surface of a Ta-based refractory metal of Embodiment 1, and includes the following steps:
[0087] Step 1, pretreatment of Ta substrate:
[0088] 1.1) Use 400#, 800#, 1500#, 2000#, and 3000# sandpaper to grind the sheet in turn.
[0089] 1.2) The sample obtained in 1.1) was mechanically polished with 0.5 μm, 0.25 μm and 0.05 μm diamond polishing agents in sequence until the surface was smooth and free of obvious scratches.
[0090] 1.3) The sample obtained in 1.2) was ultrasonically cleaned with acetone and anhydrous ethanol for 15 min in sequence and dried to obtain a pretreated Ta substrate.
[0091] 1.4) The pretreated Ta substrate is mounted on a workpiece turntable in a vacuum chamber of a magnetron sputtering device, the Re target is mounted on a DC target position, and the HfC target, Ir target and HfO2-Y2O3 target are mounted on an RF target position.
[0092] Step 2, glow sputtering cleaning process:
[0093] First, evacuate to a background vacuum of ≤5×10 -4Pa, then introduce argon, control the argon flow rate to 20sccm, control and maintain the working gas pressure to 0.5Pa, the substrate bias to -400V, and glow sputter cleaning for 25min to 30min to obtain a clean Ta substrate.
[0094] Step 3, deposit the base layer:
[0095] 3.1) Argon gas with a purity of not less than 99.9% was introduced at a flow rate of 20 sccm, a working pressure of 0.5 Pa, a sputtering power of 250 W, and a substrate bias voltage of -400 V was adjusted to deposit a 30 nm thick HfC layer as the first bottom layer.
[0096] 3.2) The substrate bias voltage was adjusted to -300 V, and a 40 nm thick HfC layer was deposited as the second bottom layer.
[0097] 3.3) The substrate bias voltage was adjusted to -200 V, and a 40 nm thick HfC layer was deposited as the third bottom layer.
[0098] 3.4) The substrate bias voltage was adjusted to -100 V, and a HfC layer with a thickness of 40 nm was deposited as the fourth primer layer to form a HfC primer layer with a gradient distribution and a thickness of 150 nm on the surface of the cleaned Ta substrate.
[0099] Step 4, depositing a diffusion barrier layer:
[0100] The argon flow rate was controlled to be 20 sccm, the working gas pressure was 0.5 Pa, the substrate bias was -100 V, the HfC target was used as the sputtering target, the sputtering power was 250 W, and a 250 nm thick HfC layer was deposited on the base layer formed in step 3.4) as a diffusion barrier layer.
[0101] Step 5, deposition of transition layer:
[0102] 5.1) Argon gas was introduced into the vacuum chamber to sputter the HfC target and the Re target simultaneously. The argon gas flow rate was 20 sccm, the gas pressure was controlled to 0.5 Pa, the substrate bias was fixed to -100 V, the sputtering power of the HfC target was adjusted to 200 W, and the sputtering power of the Re target was adjusted to 50 W. A 40 nm thick HfC-Re layer was deposited on the diffusion barrier layer formed in step 4 as a first transition layer.
[0103] 5.2) Under the conditions that the sputtering power of the HfC target is adjusted to 150 W and the sputtering power of the Re target is adjusted to 100 W, a second transition layer with a thickness of 40 nm is deposited.
[0104] 5.3) Under the conditions that the sputtering power of the HfC target is adjusted to 100 W and the sputtering power of the Re target is adjusted to 150 W, a third transition layer with a thickness of 40 nm is deposited.
[0105] 5.4) When the sputtering power of the HfC target is adjusted to 50 W and the sputtering power of the Re target is adjusted to 200 W, a fourth transition layer with a thickness of 40 nm is deposited to form a transition layer with a gradient distribution and a thickness of 160 nm on the surface of the diffusion barrier layer.
[0106] Step 6, depositing a thermal protection layer:
[0107] 6.1) Turn off the HfC target and use the Re target as the sputtering target. Control the argon flow rate to 20 sccm, the working gas pressure to 0.5 Pa, the substrate bias to -100 V, the sputtering power of the Re target to 250 W, and deposit a 400 nm thick Re layer on the transition layer formed in 5.4).
[0108] 6.2) Using Ir target as sputtering target, controlling the argon flow rate to 20 sccm, the working gas pressure to 0.5 Pa, the substrate bias to -100 V, the sputtering power of Ir target to 250 W, a 1 μm thick Ir layer is deposited on the Re layer formed in 6.1) as an anti-oxidation layer.
[0109] 6.3) Using HfO2-Y2O3 target as sputtering target, controlling the argon flow rate to 20 sccm, the working gas pressure to 0.5 Pa, the substrate bias to -100 V, the target sputtering power of HfO2-Y2O3 to 250 W, a layer of HfO2-Y2O3 with a thickness of 150 nm was deposited on the Ir layer formed in 6.2) as a ceramic protective layer.
[0110] Example 5
[0111] This embodiment provides a method for preparing a composite gradient structure coating on a surface of a Ta-based refractory metal of Embodiment 2, and includes the following steps:
[0112] Step 1, pretreatment of Ta substrate:
[0113] 1.1) Use 400#, 800#, 1500#, 2000#, and 3000# sandpaper to grind the sheet in turn.
[0114] 1.2) The sample obtained in 1.1) was mechanically polished with 0.5 μm, 0.25 μm and 0.05 μm diamond polishing agents in sequence until the surface was smooth and free of obvious scratches.
[0115] 1.3) The sample obtained in 1.2) was ultrasonically cleaned with acetone and anhydrous ethanol for 15 min in sequence and dried to obtain a pretreated Ta substrate.
[0116] 1.4) The pretreated Ta substrate is mounted on a workpiece turntable in a vacuum chamber of a magnetron sputtering device, the Re target is mounted on a DC target position, and the HfC target, Ir target and HfO2-Y2O3 target are mounted on an RF target position.
[0117] Step 2, glow sputtering cleaning process:
[0118] First, evacuate to a background vacuum of ≤5×10 -4 Pa, and then introduce argon gas with a purity of not less than 99.9%, control the argon gas flow rate to 20sccm, control and maintain the working gas pressure to 0.5Pa, the substrate bias voltage to -400V, and glow sputter cleaning for 25min to 30min to obtain a clean Ta substrate.
[0119] Step 3, deposit the base layer:
[0120] 3.1) Argon gas with a purity of not less than 99.9% is introduced at a flow rate of 20 sccm and a working pressure of 0.5 Pa. A Re target is used as a sputtering target, a sputtering power of 250 W, and a substrate bias voltage is adjusted to -400 V to deposit a 30 nm thick Re layer as the first base layer.
[0121] 3.2) The substrate bias voltage was adjusted to -300 V, and a Re layer with a thickness of 40 nm was deposited as the second bottom layer.
[0122] 3.3) The substrate bias voltage was adjusted to -200 V, and a Re layer with a thickness of 40 nm was deposited as the third bottom layer.
[0123] 3.4) The substrate bias voltage was adjusted to -100 V, and a Re layer with a thickness of 40 nm was deposited as the fourth primer layer to form a Re primer layer with a gradient distribution and a thickness of 150 nm on the surface of the clean Ta substrate.
[0124] Step 4, depositing a diffusion barrier layer:
[0125] The argon flow rate was controlled to be 20 sccm, the working gas pressure was 0.5 Pa, the substrate bias was -100 V, the HfC target was used as the sputtering target, the sputtering power was 250 W, and a 250 nm thick HfC layer was deposited on the base layer formed in step 3.4) as a diffusion barrier layer.
[0126] Step 5, deposition of transition layer:
[0127] 5.1) Argon gas was introduced into the vacuum chamber to sputter the HfC target and the Re target simultaneously. The argon gas flow rate was 20 sccm, the gas pressure was controlled to 0.5 Pa, the substrate bias was fixed to -100 V, the sputtering power of the HfC target was adjusted to 200 W, and the sputtering power of the Re target was adjusted to 50 W. A 40 nm thick HfC-Re layer was deposited on the diffusion barrier layer formed in step 4 as a first transition layer.
[0128] 5.2) Under the conditions that the sputtering power of the HfC target is adjusted to 150 W and the sputtering power of the Re target is adjusted to 100 W, a second transition layer with a thickness of 40 nm is deposited.
[0129] 5.3) Under the conditions that the sputtering power of the HfC target is adjusted to 100 W and the sputtering power of the Re target is adjusted to 150 W, a third transition layer with a thickness of 40 nm is deposited.
[0130] 5.4) When the sputtering power of the HfC target is adjusted to 50 W and the sputtering power of the Re target is adjusted to 200 W, a fourth transition layer with a thickness of 40 nm is deposited to form a transition layer with a gradient distribution and a thickness of 160 nm on the surface of the diffusion barrier layer.
[0131] Step 6, depositing a thermal protection layer:
[0132] 6.1) Turn off the HfC target and use the Re target as the sputtering target. Control the argon flow rate to 20 sccm, the working gas pressure to 0.5 Pa, the substrate bias to -100 V, the sputtering power of the Re target to 250 W, and deposit a 400 nm thick Re layer on the transition layer formed in 5.4).
[0133] 6.2) Using Ir target as sputtering target, controlling the argon flow rate to 20 sccm, the working gas pressure to 0.5 Pa, the substrate bias to -100 V, the sputtering power of Ir target to 250 W, a 1 μm thick Ir layer is deposited on the Re layer formed in 6.1) as an anti-oxidation layer.
[0134] 6.3) Using HfO2-Y2O3 target as sputtering target, controlling the argon flow rate to 20 sccm, the working gas pressure to 0.5 Pa, the substrate bias to -100 V, the target sputtering power of HfO2-Y2O3 to 250 W, a layer of HfO2-Y2O3 with a thickness of 150 nm was deposited on the Ir layer formed in 6.2) as a ceramic protective layer.
[0135] Example 6
[0136] This embodiment provides a method for preparing a composite gradient structure coating on a surface of a Ta-based refractory metal of embodiment 3, and includes the following steps:
[0137] Step 1, pretreatment of Ta substrate:
[0138] 1.1) Use 400#, 800#, 1500#, 2000#, and 3000# sandpaper to grind the sheet in turn.
[0139] 1.2) The sample obtained in 1.1) was mechanically polished with 0.5 μm, 0.25 μm and 0.05 μm diamond polishing agents in sequence until the surface was smooth and free of obvious scratches.
[0140] 1.3) The sample obtained in 1.2) was ultrasonically cleaned with acetone and anhydrous ethanol for 15 min in sequence and dried to obtain a pretreated Ta substrate.
[0141] 1.4) The pretreated Ta substrate is mounted on a workpiece turntable in a vacuum chamber of a magnetron sputtering device, the Ta target and the Re target are mounted on a DC target position, and the HfC target, the Ir target and the HfO2-Y2O3 target are mounted on an RF target position.
[0142] Step 2, glow sputtering cleaning process:
[0143] First, evacuate to a background vacuum of ≤5×10 -4 Pa, then introduce argon, control the argon flow rate to 20sccm, control and maintain the working gas pressure to 0.5Pa, the substrate bias to -400V, and glow sputter cleaning for 25min to 30min to obtain a clean Ta substrate.
[0144] Step 3, deposit the base layer:
[0145] 3.1) Argon gas with a purity of not less than 99.9% was introduced at a flow rate of 20 sccm, a working pressure of 0.5 Pa, a sputtering power of 250 W, and a substrate bias voltage of -400 V. A Ta layer with a thickness of 30 nm was deposited as the first bottom layer.
[0146] 3.2) The substrate bias voltage was adjusted to -300 V, and a 40 nm thick Ta layer was deposited as the second bottom layer.
[0147] 3.3) The substrate bias voltage was adjusted to -200 V, and a 40 nm thick Ta layer was deposited as the third bottom layer.
[0148] 3.4) The substrate bias voltage was adjusted to -100 V, and a Ta layer with a thickness of 40 nm was deposited as the fourth primer layer to form a Ta primer layer with a gradient distribution and a thickness of 150 nm on the surface of the cleaned Ta substrate.
[0149] Step 4, depositing a diffusion barrier layer:
[0150] The argon flow rate was controlled to be 20 sccm, the working gas pressure was 0.5 Pa, the substrate bias was -100 V, the HfC target was used as the sputtering target, the sputtering power was 250 W, and a 250 nm thick HfC layer was deposited on the base layer formed in step 3.4) as a diffusion barrier layer.
[0151] Step 5, deposition of transition layer:
[0152] 5.1) Argon gas was introduced into the vacuum chamber to sputter the HfC target and the Re target simultaneously. The argon gas flow rate was 20 sccm, the gas pressure was controlled to 0.5 Pa, the substrate bias was fixed to -100 V, the sputtering power of the HfC target was adjusted to 200 W, and the sputtering power of the Re target was adjusted to 50 W. A 40 nm thick HfC-Re layer was deposited on the diffusion barrier layer formed in step 4 as a first transition layer.
[0153] 5.2) Under the conditions that the sputtering power of the HfC target is adjusted to 150 W and the sputtering power of the Re target is adjusted to 100 W, a second transition layer with a thickness of 40 nm is deposited.
[0154] 5.3) Under the conditions that the sputtering power of the HfC target is adjusted to 100 W and the sputtering power of the Re target is adjusted to 150 W, a third transition layer with a thickness of 40 nm is deposited.
[0155] 5.4) When the sputtering power of the HfC target is adjusted to 50 W and the sputtering power of the Re target is adjusted to 200 W, a fourth transition layer with a thickness of 40 nm is deposited to form a transition layer with a gradient distribution and a thickness of 160 nm on the surface of the diffusion barrier layer.
[0156] Step 6, depositing a thermal protection layer:
[0157] 6.1) Turn off the HfC target and use the Re target as the sputtering target. Control the argon flow rate to 20 sccm, the working gas pressure to 0.5 Pa, the substrate bias to -100 V, the sputtering power of the Re target to 250 W, and deposit a 400 nm thick Re layer on the transition layer formed in 5.4).
[0158] 6.2) Using Ir target as sputtering target, controlling the argon flow rate to 20 sccm, the working gas pressure to 0.5 Pa, the substrate bias to -100 V, the sputtering power of Ir target to 250 W, a 1 μm thick Ir layer is deposited on the Re layer formed in 6.1) as an anti-oxidation layer.
[0159] 6.3) Using HfO2-Y2O3 target as sputtering target, controlling the argon flow rate to 20 sccm, the working gas pressure to 0.5 Pa, the substrate bias to -100 V, the target sputtering power of HfO2-Y2O3 to 250 W, a layer of HfO2-Y2O3 with a thickness of 150 nm was deposited on the Ir layer formed in 6.2) as a ceramic protective layer.
[0160] Comparative Example 1
[0161] The difference between this comparative example and Example 4 is only that:
[0162] In this comparative example, when depositing the base layer, the substrate bias voltage is not adjusted, that is, the substrate bias voltage is maintained at -400V.
[0163] Comparative Example 2
[0164] The difference between this comparative example and Example 4 is only that:
[0165] In this comparative example, when depositing the base layer, the sputtering power of the HfC target and the Re target was not adjusted, that is, the sputtering power of the HfC target was kept at 200W, and the sputtering power of the Re target was kept at 50W.
[0166] Comparative Example 3
[0167] The difference between this comparative example and Example 4 is only that:
[0168] In this comparative example, no primer layer was deposited.
[0169] Experimental Section
[0170] (I) Microscopic morphology test
[0171] The present invention takes the composite gradient structure coating prepared in Example 4 as an example, and performs a scanning electron microscope test on the cross section of the coating. The test results are as follows: Figure 2 shown.
[0172] Figure 2 This is a cross-sectional scanning electron microscope image of the composite gradient structure coating prepared in Example 4.
[0173] Depend on Figure 2 It can be seen that the thickness of the composite gradient structure coating prepared in Example 4 is 1.97 μm, and the coating has an obvious three-layer composite gradient structure.
[0174] It can also be seen that in the composite gradient structure coating prepared in Example 4, the innermost layer, that is, the closest to the Ta substrate, is the primer layer and the HfC layer, and the interface between the two is not obvious, indicating that the transition is sufficient and there is no abrupt interface. The middle layer is the Ir layer and the Re layer, which are also tightly combined without a dividing line. The Ir / Re layer is a small and tight columnar crystal. The outermost layer HfO2-Y2O3 is about 200nm. The cross-section of the coating is flat, the structure is dense, there is no gap, and it is tightly combined with the substrate.
[0175] Based on the above, it can be seen that the composite gradient structure coating formed on the surface of the Ta-based refractory metal by the preparation method of the present invention has a fully tight transition between the layers and a good bonding force with the substrate.
[0176] (ii) XRD test
[0177] The present invention takes the composite gradient structure coating prepared in Example 5 as an example, and performs XRD test on the surface of the coating, and the test results are as follows: Figure 3 shown.
[0178] Figure 3 This is the XRD spectrum of the composite gradient structure coating prepared in Example 5.
[0179] Figure 3 Peaks of Ir, Re, HfC coatings and Ta substrate can be seen, among which the preferred growth direction of Ir coating is <111> , the preferred growth direction of the Re coating is <002> This indicates that the composite gradient structure coating prepared by the preparation method of the present invention has good growth quality between each layer of the coating, and also verifies that the Ir / Re layer exists in the form of fine and compact columnar crystals. No peaks of HfO2 and Y2O3 were detected, indicating that the oxide ceramic exists in an amorphous form.
[0180] (III) Thermal protection performance test
[0181] In order to verify the thermal protection performance of the composite gradient structure coating prepared by the present invention, taking the composite gradient structure coating prepared in Example 6 as an example, the obtained coating was subjected to high-temperature annealing at 1200°C for 30 minutes to simulate the high-temperature diffusion process.
[0182] 1) Scanning electron microscope test
[0183] The present invention conducted a scanning electron microscope test on the cross section of the composite gradient structure coating after annealing in the above-mentioned embodiment 6. The test results are as follows: Figure 4 shown.
[0184] Figure 4This is a cross-sectional scanning electron microscope image of the composite gradient structure coating prepared in Example 6 after high temperature annealing. It can be seen that after high temperature annealing, the composite gradient structure coating prepared in Example 6 did not fall off and the substrate was not damaged, and the coating and the substrate were still tightly bonded. This shows that the composite gradient structure coating prepared in the present invention has excellent thermal protection performance.
[0185] 2) Scratch test
[0186] The present invention also conducted a scratch test on the surface of the composite gradient structure coating prepared in Example 6 before and after annealing, and conducted an electron backscatter diffraction test on the coating after the scratch test, and the test results are as follows: Figure 5 shown.
[0187] Figure 5 The scratch backscattering images of the composite gradient structure coating prepared in Example 6 before and after high-temperature annealing and after the scratch test; wherein, (a) is the scratch backscattering image of the composite gradient structure coating prepared in Example 6 before and after the scratch test; (b) is the scratch backscattering image of the composite gradient structure coating prepared in Example 6 after the high-temperature annealing and after the scratch test.
[0188] By comparison Figure 5 As can be seen from Figures (a) and (b), peeling occurs at the initial position of loading before annealing, while peeling occurs in the middle part of loading after annealing, that is, when the load is larger, indicating that the bonding strength of the coating is improved after annealing, and no brittle peeling occurs during the annealing process due to the difference in thermal expansion coefficient, and the bonding strength of the coating is still strong at high temperature.
[0189] The present invention also subjected the coatings prepared in Comparative Examples 1, 2 and 3 to high temperature annealing at 1200°C for 30 minutes to simulate the high temperature diffusion process. The present invention conducted a scanning electron microscope test on the cross-section of the composite gradient structure coatings after annealing in Comparative Examples 1, 2 and 3. The results showed that after annealing, the coatings prepared in Comparative Examples 1 to 3 all experienced obvious coating shedding and substrate damage. Taking Comparative Example 3 as an example, Figure 6 The cross-sectional scanning electron microscope image of the coating prepared in comparative example 3 after high temperature annealing shows that the coating prepared in comparative example 3 has obvious fragmentation after high temperature annealing. This indicates that the preparation operation of gradually reducing the bias voltage from the inside to the outside of the base layer on the Ta substrate and the gradient distribution of the composition of the transition layer play an important role in improving the bonding strength between the coating and the substrate, as well as the bonding strength between the coating layers, and are the key to improving the bonding strength of the coating base film and the high temperature protection performance of the present invention.
[0190] The above test results prove that after high-temperature annealing, the substrate and the coating do not fall off or break, which indicates that the coating prepared by the preparation method of the present invention can effectively improve the high-temperature protection performance of the substrate.
[0191] Obviously, the above embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
Claims
1. A composite gradient structure coating on the surface of a Ta-based refractory metal, characterized in that: The composite gradient structure coating is arranged on the Ta substrate, and the composite gradient structure coating includes a primer layer, a diffusion barrier layer, a transition layer and a thermal protection layer which are sequentially stacked from the inside to the outside on the Ta substrate; The composition of the bottom layer is metal or metal carbide, and the bias pressure of the bottom layer gradually decreases from the inside to the outside on the Ta substrate; The diffusion barrier layer is composed of metal carbide; The transition layer comprises metal carbides and Re; and from the inside to the outside of the transition layer, the content of metal carbides decreases in a gradient, and the content of Re increases in a gradient; The thermal protection layer is composed of a Re layer, an Ir layer and a HfO2-Y2O3 layer from the inside to the outside.
2. The composite gradient structure coating according to claim 1, characterized in that: The metal is one or both of Re and Ta; The metal carbide is one or both of HfC and TaC.
3. The composite gradient structure coating according to claim 1, characterized in that: The thickness of the Re layer is 400nm to 500nm; The thickness of the Ir layer is 800nm to 1500nm; The thickness of the HfO2-Y2O3 layer is 100nm to 300nm.
4. The composite gradient structure coating according to claim 1, characterized in that: The thickness of the primer layer is 100nm to 500nm; The thickness of the diffusion barrier layer is 100nm to 500nm; The thickness of the transition layer is 50nm-500nm.
5. A method for preparing a composite gradient structure coating according to any one of claims 1 to 4, characterized in that: The following steps are involved: Polishing and cleaning the Ta substrate to obtain a pretreated Ta substrate; The pretreated Ta substrate is subjected to glow sputtering cleaning treatment to obtain a clean Ta substrate; In an argon atmosphere, magnetron sputtering technology is used, a metal target or a metal carbide target is used as a sputtering target, and a substrate bias voltage is controlled to gradually decrease, and a primer layer is deposited on the surface of the clean Ta substrate; Using a metal carbide target as a sputtering target, depositing a diffusion barrier layer on the surface of the primer layer; Using a metal carbide target and a Re target as co-sputtering targets, depositing on the surface of the diffusion barrier layer at the same time, during the deposition process, gradually reducing the sputtering power of the metal carbide target and gradually increasing the sputtering power of the Re target, so as to deposit a transition layer with a decreasing metal carbide component gradient and an increasing Re component gradient on the surface of the diffusion barrier layer; A Re target, an Ir target and a HfO2-Y2O3 target are used as sputtering targets in sequence, and a Re layer, an Ir layer and a HfO2-Y2O3 layer are deposited in sequence on the surface of the transition layer to form a thermal protection layer composited by a Re layer, an Ir layer and a HfO2-Y2O3 layer on the surface of the transition layer.
6. The preparation method according to claim 5, characterized in that: When depositing the base layer, first evacuate the vacuum to a background vacuum of ≤5×10 -4 Pa, then introduce argon to maintain the working pressure at 0.2Pa~1.5Pa; During sputtering deposition, the sputtering power is fixed at 200W to 300W, and the argon gas flow rate is 10sccm to 30sccm; First, a first primer layer with a thickness of 20 nm to 100 nm is deposited under the condition that the substrate bias voltage is -400 V to -500 V; Then, the substrate bias voltage is adjusted to -300V to -400V, and a second primer layer with a thickness of 20nm to 100nm is deposited; Then, the substrate bias voltage is adjusted to -200V to -300V, and a third bottom layer with a thickness of 20nm to 100nm is deposited; Finally, the substrate bias voltage is adjusted to -100V to -200V, and a fourth bottom layer with a thickness of 20nm to 100nm is deposited to obtain the bottom layer formed by the first bottom layer, the second bottom layer, the third bottom layer and the fourth bottom layer.
7. The preparation method according to claim 5, characterized in that: When depositing the transition layer, argon gas is introduced, the argon gas flow rate is controlled to be 10 sccm to 30 sccm, the working gas pressure is controlled to be 0.2 Pa to 1.5 Pa, and the substrate bias voltage is fixed to be -90 V to -120 V; Prior to depositing a first transition layer with a thickness of 20 nm to 100 nm under the conditions that the sputtering power of the metal carbide target is 200 W to 300 W and the sputtering power of the Re target is 50 W to 100 W; Then, a second transition layer with a thickness of 20 nm to 100 nm is deposited under the condition that the sputtering power of the metal carbide target is adjusted to 100 W to 200 W and the sputtering power of the Re target is adjusted to 100 W to 150 W; Then, the sputtering power of the metal carbide target is adjusted to 50W-100W, and the sputtering power of the Re target is adjusted to 150W-200W, and a third transition layer with a thickness of 20nm-100nm is deposited; Finally, under the conditions that the sputtering power of the metal carbide target is adjusted to 20W-50W and the sputtering power of the Re target is adjusted to 200W-250W, a fourth transition layer with a thickness of 20nm-100nm is deposited to obtain the transition layer formed by the first transition layer, the second transition layer, the third transition layer and the fourth transition layer.
8. The preparation method according to claim 5, characterized in that: When depositing the diffusion barrier layer, argon gas is introduced, the argon gas flow rate is controlled to be 10 sccm to 30 sccm, the working gas pressure is controlled to be 0.2 Pa to 1.5 Pa; the sputtering power is 200 W to 300 W, and the substrate bias voltage is -90 V to -120 V.
9. The preparation method according to claim 5, characterized in that: When depositing the thermal protection layer, argon gas is introduced, the argon gas flow rate is controlled to be 10 sccm to 30 sccm, the working gas pressure is controlled to be 0.2 Pa to 1.5 Pa, and the substrate bias voltage is -90 V to -120 V; When depositing the Re layer in the thermal protection layer, the sputtering power is 200W to 250W; When depositing the Ir layer in the thermal protection layer, the sputtering power is 200W to 300W; When depositing the HfO2-Y2O3 layer in the thermal protection layer, the sputtering power is 200W-300W.
10. The preparation method according to claim 5, characterized in that: During the glow sputtering cleaning process, the vacuum is first evacuated to a background vacuum of ≤5×10 -4 Pa, then introduce argon, control the argon flow rate to 10sccm~30sccm, control and maintain the working gas pressure to 0.2Pa~1.5Pa, the substrate bias voltage to -300V~-500V, and the cleaning time ≥15min.
Citation Information
Patent Citations
Refractory metal surface layered composite Ir / W high-temperature oxidation-resistant coating and preparation method thereof
CN108070859A
Preparation method of ablation-resistant refractory metal tantalum and nitride multilayer coating of ablation-resistant refractory metal tantalum
CN118422145A
Metal carbide coating to prevent hot corrosion of boiler overheater in power station
CN1274767A
Process for coating a part with an oxidation-protective coating
US20140004271A1
Oxidation resistance coating system for refractory metals
US6200691B1
Cited By
Tantalum-based multilayer composite powder, preparation method thereof and cold spraying coating material
CN120362484A
Marine climate environment-torsion load coupling test equipment
CN120594276A